Detection, Identification and Diagnostic Characterization of the Staphylococcal Small Colony-Variant (SCV) Phenotype - Karsten Becker (Antibiotics, 2023)
While modern molecular methods have decisively accelerated and improved microbiological diagnostics, phenotypic variants still pose a challenge for their detection, identification and characterization. This particularly applies if they are unstable and hard to detect, which is the case for the small-colony-variant (SCV) phenotype formed by staphylococci. On solid agar media, staphylococcal SCVs are characterized by tiny colonies with deviant colony morphology. Their reduced growth rate and fundamental metabolic changes are the result of their adaptation to an intracellular lifestyle, regularly leading to specific auxotrophies, such as for menadione, hemin or thymidine. These alterations make SCVs difficult to recognize and render physiological, biochemical and other growth-based methods such as antimicrobial susceptibility testing unreliable or unusable. Therefore, diagnostic procedures require prolonged incubation times and, if possible, confirmation by molecular methods. A special approach is needed for auxotrophy testing. However, standardized protocols for SCV diagnostics are missing. If available, SCVs and their putative parental isolates should be genotyped to determine clonality. Since their detection has significant implications for the treatment of the infection, which is usually chronic and relapsing, SCV findings should be specifically reported, commented on, and managed in close collaboration with the microbiological laboratory and the involved clinicians.